2016
DOI: 10.1007/s10485-016-9471-x
|View full text |Cite
|
Sign up to set email alerts
|

A New Characterisation of Groups Amongst Monoids

Abstract: Abstract. We prove that a monoid M is a group if and only if, in the category of monoids, all points over M are strong. This sharpens and greatly simplifies a result of Montoli, Rodelo and Van der Linden [8] which characterises groups amongst monoids as the protomodular objects.In their article [8], Montoli, Rodelo and Van der Linden introduce, amongst other things, the concept of a protomodular object in a finitely complete category C as an object Y P C over which all points are stably strong. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…All split extensions over a bialgebra Y admit a join decomposition if and only if Y is a Hopf algebra. This result is along the lines of, and is actually a variation on, a similar characterization of groups among monoids, recently obtained in [12,7]. There the authors show 2010 Mathematics Subject Classification.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…All split extensions over a bialgebra Y admit a join decomposition if and only if Y is a Hopf algebra. This result is along the lines of, and is actually a variation on, a similar characterization of groups among monoids, recently obtained in [12,7]. There the authors show 2010 Mathematics Subject Classification.…”
Section: Introductionsupporting
confidence: 78%
“…Applying the functor G, we regain the original split extension, since G is a right adjoint, thus preserves kernels; but G also preserves jointly extremally epimorphic pairs by Proposition 3.3, so that the pair pk, sq is jointly extremally epimorphic. As a consequence, all split extensions over the monoid GpY q are strong, and GpY q is protomodular [7].…”
Section: A Universal Characterization Of Cocommutative Hopf Algebrasmentioning
confidence: 99%
See 2 more Smart Citations
“…A related line of research is to identify exactness properties of an object which describe certain algebraically defined members of a variety. A striking positive result in this area is given in [77,40], where it is shown that groups can be identified in the variety of monoids using a first-order exactness property.…”
Section: Exactness Properties For Mal'tsev Conditionsmentioning
confidence: 99%